Genome-wide gene expression profiles of thyroid carcinoma: Identification of molecular targets for treatment of thyroid carcinoma - Nikolova, Dragomira Nikolaeva; Zembutsu, Hitoshi; Sechanov, Tanio; Vidinov, Kalin; Kee, Low Siew; Ivanova, Radina; Becheva, Elitza; Kocova, Mirjana; Toncheva, Draga; Nakamura, Yusuke (Spandidos Publications, 2008)
In order to clarify the molecular mechanism involved in thyroid carcinogenesis and to identify candidate molecular targets for diagnosis and treatment, we analyzed genome-wide gene expression profiles of 18 papillary thyroid carcinomas with a microarray representing 38,500 genes in combination with laser microbeam microdissection. We identified 243 transcripts that were commonly up-regulated and 138 transcripts that were down-regulated in thyroid carcinoma. Among these 243 transcripts identified, only 71 transcripts were reported as up-regulated genes in previous microarray studies, in which bulk cancer tissues and normal thyroid tissues were used for the analysis. We further selected genes that were overexpressed very commonly in thyroid carcinoma, though were not expressed in the normal human tissues examined. Among them, we focused on the regulator of G-protein signaling 4 (RGS4) and knocked-down its expression in thyroid cancer cells by small-interfering RNA. The effective down-regulation of its expression levels in thyroid cancer cells significantly attenuated viability of thyroid cancer cells, indicating the significant role of RGS4 in thyroid carcinogenesis. Our data should be helpful for a better understanding of the tumorigenesis of thyroid cancer and could contribute to the development of diagnostic tumor markers and molecular-targeting therapy for patients with thyroid cancer.